LA INTELIGENCIA EMOCIONAL EN EL DESARROLLO SOCIAL DE LOS NIÑOS DE QUINTO AÑO DEL CENTRO EDUCATIVO COMUNITARIO RIO JUBAL ALAUSÍ PERIODO 2017 – 2018 - Gualancañay Pagalo, Bertha Verónica (2019)
The present investigative work was carried out in the Community Educational Center "Rio Jubal", located in the canton of Alausí, province of Chimborazo, in the academic year 2018-2019, which aims to determine the influence of Emotional Intelligence on the development of the children of the fifth year of basic of the Community Educational Center "Rio Jubal", for which a situational diagnosis was made of the reality having as a study population the children of the aforementioned basic year. Using data collection techniques such as direct observation, it made it possible to demonstrate the existence of children who have not adequately developed their emotional intelligence, since 62% of them can not always adequately recognize their emotions and only 38% of the students observed have an adequate emotional intelligence which has caused that they do not show an adequate level of social development that was diagnosed based on the observable categories such as: independence, initiative, acceptance, cooperation, conflict resolution, before which a series has been proposed of activities aimed at reducing the problem detected, thus obtaining positive results because after this process the social development of the children was significantly improved.